Evaluation of Listeria spp. and Listeria monocytogenes in selected vegetable farms - Ponniah, Jeyaletchumi; Robin, Tunung; Paie, Margaret Selina; Chai, Lay Ching; Radu, Son; Mohamad Ghazali, Farinazleen; Cheah, Yoke Kqueen; Nishibuchi, Mitsuaki; Nakaguchi, Yoshitsugu; Malakar, Pradeep Kumar (Malaysian Agricultural Research and Development Institute (MARDI), 2011)
The aim of the study was to examine the prevalence of Listeria spp. and Listeria monocytogenes in soil, poultry manure, irrigation water, and freshly harvested vegetables from three vegetable farms in Cameron Highlands. A total of 177 samples including environmental and vegetable samples were collected. Among the environmental samples (n = 94), poultry manure was found to have a higher prevalence of Listeria spp. and L. monocytogenes at 77.8% and 61.1% respectively using the MPN-PCR analysis procedure. Soil samples were also found to harbour Listeria spp. and L. monocytogenes at 47.6% and 38.1% respectively. Irrigation water sampled from the farms were found to be free from Listeria spp. Both Listeria spp. and L. monocytogenes were also detected in 24% and 12% of swabs done at the three farms respectively. Among the freshly harvested vegetables, Listeria spp. was detected in cabbages (30%), cucumber (20%), yardlong beans (10%) and carrots (10%) whereas L. monocytogenes was detected in cabbages (10%), yardlong beans (10%) and carrots (10%) using the MPN-PCR analysis procedure. The present results signify that Listeria spp. poses a potential risk for raw vegetable consumption in Malaysia. The study also provides baseline data on Listeria spp. contamination at farm level.